Pemberdayaan Kelompok Usaha Kuliner Ikan Bakar Pantai Blimbingsari Melalui Pelatihan dan Pembuatan SOP Sequence of Service Dalam Upaya Peningkatan Kualitas Pelayanan - Nurhalimah Nurhalimah; Rudi Tri Handoko; Auda Nuril Zazilah; Firda Rachma Amalia; Reni Nur Jannah (Journal of Community Development, 2025)
Banyuwangi develops the tourism sector intensively by strengthening tourism businesses and the creative economy by optimizing the potential of Banyuwangi's typical culinary products. The tourism potential of Blimbingsari beach in the form of grilled fish culinary tourism is one of the magnets for tourists to visit Blimbingsari. Cleanliness and grooming of waiters who serve visitors need to be improved. The results of observations in the field show that the cleanliness of the grilled fish culinary stalls at Blimbingsari beach is not being maximized. So training is needed regarding the sequence of service which aims to improve service quality. The methods used in this PkM activity are observation, needs analysis, providing training and creating a sequence of service SOP. Training activities in the Blimbingsari beach grilled fish culinary business group are not only provided with direct training and practice regarding the sequence of service, but also how to greet and groom properly, use appropriate and hygienic cutleries, make napkin art to beautify the appearance of visitors' dining tables, as well as arranging SOP sequence of service to provide excellent service to all visitors who enjoy the Blimbingsari beach grilled fish culinary tour. By increasing of knowledge and skill as 70% in service quality, it is hoped that the number of visitors who will enjoy the Blimbingsari beach grilled fish culinary tour will increase.